Iron Ore Company (IOC) of Canada versus the Innu : perspective of a dispute from a local lens - Lasserre, Frédéric; Têtu, Pierre-Louis (LexisNexis, 2019)
This study investigates conflict resolution mechanisms between the Iron Ore Company of Canada (hereafter "IOC"), an exploration and mining company, and the Innu of Quebec & Labrador, in their fight against land degradation without agreements or compensatory sums. Through a multidisciplinary approach that includes law, social & environmental studies, we will highlight themain problems, challenges and consequences of the conflict resolution mechanisms. Based on the UN Guiding Principles on Business and Human Rights, we will look at how to protect and respectIndigenous people, and remedy their conflicts with the mining industry. More specifically, we will first present and compare various Indigenous land claim agreements, the environmentalregulations and taxation system as they apply to mining projects in Quebec and Newfoundland &Labrador. Next, we will discuss the conflict resolution mechanisms, methods and managementdeveloped by both IOC Canada and the Innu. Finally, we will discuss the fundamental rights of the Innu, through the 2004 Haida Nation v. British Columbia judgment and the “Honour of theCrown,” that was invoked as a central principle in the settlement of Indigenous consultationrequests, even in the absence of a treaty. The creation or need for new mechanisms for disputeprevention and resolution will also be discussed. 0